COVID-19 – compliant – IVF: reorganized clinical practice taking into account the pandemic. (3rd June 2022) - Greco, Ermanno; Donno, Valeria; Greco, Pierfrancesco; Arrivi, Cristina; Litwicka, Katerina; Varricchio, Maria Teresa
Abstract: Purpose: The need for protective measures during the COVID-19 pandemic forced assisted reproduction centers to adopt new protocols in order to reduce the risk of infection for patients and staff. A COVID-19 Compliant IVF ( in vitro fertilization) program based on the use of follitropin delta to induce ovarian stimulation and fixed protocol with GnRH (Gonadotropin-Releasing Hormone) antagonists was applied to demonstrate the efficacy of this program in reducing the necessity of patients to be present within the clinic while maintaining the expected success rate. Methods: The program was applied to 100 patients (women aged between 20 and 40 years, at their first IVF cycle): pretreatment assessment was carried out via video conference and clinical documentations were sent by email. Ovarian stimulation was based on doses of Follitropin delta selected on the basis of body weight and serum AMH (Anti-Müllerian Hormone). The study population was then compared with historical controls to assess the percentage of patients receiving fresh embryo transfer. Finally, a questionnaire was proposed to assess patient satisfaction. Results: The ovarian stimulation protocol with a fixed dose of follitropin delta led to an optimal ovarian response (8–14 oocytes) in 54% of the women included in the study. The rate of hyper response was 15% and was significantly lower that what reported in the control group (26.8%, p < .05). The good control of ovarian response to stimulation is the reason for the large percentage of cycles associated with fresh embryo transfer (84%, n 84/100). The rate of fresh embryo transfer was significantly higher that what reported for the control population (68.5%, p < .05). In 40 out of 84 patients, blastocysts were available for the fresh embryo transfer procedure. Eighty-five percent (89/100) of survey responders reported being extremely satisfied with the simplified approach to the IVF cycle because of reduced number of visits, easy management of working hours and reduction in travel costs. Conclusions: The use of follitropin delta and fixed protocol with GnRH antagonist in COVID-19 – Compliant IVF program is associated to a low percentage of patients developing excessive ovarian response compared to conventional strategy and a very good level of patient satisfaction. Beyond the pandemic, the new approach to ovarian stimulation, modern technologies and telemedicine could play a key role in bridging the gap between different geographic areas and could offer advantages such as increased accessibility, cost saving and patient satisfaction.